Exploring links between the sustainability performance of urban public transport and land use in international cities - Graham Currie; Chris De Gruyter (Journal of Transport and Land Use)
Sustainability is a major driver of world policy for cities, and public transport is said to be a more sustainable mode of travel than other modes. But how do public transport (PT) systems in different cities compare to each other? This paper measures the relative sustainability of public transport systems between cities rather than between modes within cities. However, its primary focus is to explore the extent to which public transport sustainability is influenced by land use. Do cities with low-density land use automatically have poor sustainability performance? Do high-density megacities always have good sustainability performance relative to other cities? Does land use mean some cities cannot improve sustainability performance? These are some of the questions this research seeks to explore through an empirical study of land use and PT sustainability metrics using correlation/cross sectional and regression analyses. Results suggest that westernized, developed countries (Western Europe, North America, and Oceania) have good environmental and social sustainability performance but poor service effectiveness and economic performance. Asia and Latin America perform the other way around, better on economic and service effectiveness and worse on social and economic performance. Eastern Europe is the one region with higher sustainability performance all around. Prague, Dakar and Tokyo are at the top of 98 cities studied, while Dubai, Shizuoka (Japan), Denver, and Johannesburg perform the worst.